2019
DOI: 10.1088/1674-1056/ab4041
|View full text |Cite
|
Sign up to set email alerts
|

Flexible rGO/Fe3O4 NPs/polyurethane film with excellent electromagnetic properties*

Abstract: Large-area and flexible reduced graphene oxide (rGO)/Fe3O4 NPs/polyurethane (PU) composite films are fabricated by a facile solution-processable method. The monolayer assembly of Fe3O4 nanoparticles with a high particle-stacking density on the graphene oxide (GO) sheets is achieved by mixing two immiscible solutions of Fe3O4 nanoparticles in hexane and GO in dimethylformide (DMF) by a mild sonication. The x-ray diffraction and Raman spectrum confirm the reduced process of rGO by a simple thermal treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Flexible electronics enable electronic devices to maintain their original performance despite being twisted, folded, stretched, and undergoing other shape changes [1][2][3]. They can be used as wearable devices, electronic skin, flexible displays, and more [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible electronics enable electronic devices to maintain their original performance despite being twisted, folded, stretched, and undergoing other shape changes [1][2][3]. They can be used as wearable devices, electronic skin, flexible displays, and more [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Therefore, numerous methods have been researched to rationally synthesize and change the structure of GO composites. [26][27][28][29][30] Several materials such as metals and ferrites can be applied to improve the structure and microwave absorption of GO. Previous studies have also shown that by the combination of GO with magnetic metallic nanoparticle ma-terials, its relative permittivity and permeability can achieve the maximum absorption of microwave in a wide frequency range.…”
Section: Introductionmentioning
confidence: 99%